Performance of twisted tape absorber-based photovoltaic thermal systems in clockwise and counterclockwise configurations - Abdalrahman M.O. Al-Karboly; Adnan Ibrahim; Anas Al-Tarabsheh; Anwer B. Al-Aasam; Ali H.A. Al-Waeli; Ahmad Fazlizan; Kamaruzzaman Sopian (Case Studies in Thermal Engineering)
The main limitation of conventional photovoltaic thermal (PVT) collectors is the method of establishing heat transfer to extract trapped heat in the photovoltaic (PV) module. Therefore, this study improved the electrical efficiency of PV modules by introducing a novel twisted tube absorber-based PVT system in anticlockwise (PVT-CCW) and clockwise (PVT-CW) configurations. Numerous solar irradiance levels (200 W/m2, 400 W/m2, 600 W/m2, 800 W/m2, and 1000 W/m2) were examined using an indoor solar simulator, a nanofluid containing water and 0.5 vol% SiC, and mass flow rates from 0.005 kg/s to 0.04 kg/s. This analysis involved investigating various factors to demonstrate the improved performance of PVT-CCW configuration, including thermal and electrical efficiencies, temperature, and current-voltage (I-V) with PV properties. Exceptional peak thermal (82.36 %) and electrical efficiencies (10.5 %) indicated a significant 38 % improvement in electricity output than traditional PV systems. This study presents a novel (PVT) system that combines counterclockwise (CCW) twisted tape technology with SiC nanofluids. The use of SiC nanofluids enhances thermal conductivity and disrupts the thermal boundary layer, significantly improving heat transfer. These findings advance the understanding of PVT system performance and open new avenues for optimizing renewable energy technologies, making this research a valuable contribution to the field.